Legal Aspects of the Implementation of New Voting Technologies in Kyrgyz Republic - N. S. Chimarov (Евразийская интеграция: экономика, право, политика, 2019)
The article discusses the technology of biometric identification of voters in Kyrgyzstan. The author analyzes the legal consolidation of this technology. This experience is seems important for other Eurasian countries.